2022
DOI: 10.25259/ijasm_13_2022
|View full text |Cite
|
Sign up to set email alerts
|

Coping styles and subjective well-being of indian civil aircrew in the context of COVID-19

Abstract: Objectives: The novel coronavirus (COVID-19) infection has emerged into a widespread pandemic that stalled the world. Humanitarian missions like Vande Bharat during the first wave of COVID-19 and passenger as well as cargo services during its second wave were carried out extensively by civil aircrew. Operating under such challenging circumstances is likely to affect the well-being and psychological health of the aircrew. Exploring different coping strategies adopted by civil aircrew and assessment of their sub… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 13 publications
0
0
0
Order By: Relevance
“…As expected, the results showed that neuroticism was negatively associated with psychological well-being and extraversion, agreeableness, and conscientiousness were strongly, positively associated with psychological wellbeing. There are many researches in the literature supporting these findings (e.g., Othman, Bahri Yusof, Din, & Zakaria, 2016;Apostolou, 2016;Kokko, Tolvanen, & Pulkkinen, 2015;Singh, Singh, & Singh, 2012;Grant, et al, 2009;Chaturvedula & Joseph, 2007), however, our special interest is in those researches targeting collectivist cultures. Thus, in a study conducted on Iranian college students, Vakili Mobarakeh et al (2015) found similar results and argued that in collectivist cultures, as in individualist ones, people who are less neurotic and more agreeable are more likely sociable and establish social relationships.…”
Section: Discussionmentioning
confidence: 80%
“…As expected, the results showed that neuroticism was negatively associated with psychological well-being and extraversion, agreeableness, and conscientiousness were strongly, positively associated with psychological wellbeing. There are many researches in the literature supporting these findings (e.g., Othman, Bahri Yusof, Din, & Zakaria, 2016;Apostolou, 2016;Kokko, Tolvanen, & Pulkkinen, 2015;Singh, Singh, & Singh, 2012;Grant, et al, 2009;Chaturvedula & Joseph, 2007), however, our special interest is in those researches targeting collectivist cultures. Thus, in a study conducted on Iranian college students, Vakili Mobarakeh et al (2015) found similar results and argued that in collectivist cultures, as in individualist ones, people who are less neurotic and more agreeable are more likely sociable and establish social relationships.…”
Section: Discussionmentioning
confidence: 80%
“…An employee that believe he has the ability and self-efficacy to perform his job and take proactive steps to invest in training and self-development programs to add to his skills repertoire reports a better sense of well-being (Plomp et al, 2016). A study done by Chaturvedula et al (2018) among Remotely Piloted Aircraft System crew found that the personnel who have high proficiency in their job experience positive emotions and increase well-being. The literature also shows HR policies that encourage training among employees create positive impact on employee's well-being and overall productivity (Nielsen et al, 2017).…”
Section: The Independent Variablesmentioning
confidence: 99%